A longitudinal assessment of diabetes autoantibodies in the SEARCH for diabetes in youth study. Issue 7 (30th August 2022) - Merjaneh, Lina; Dolan, Lawrence M.; Suerken, Cynthia K.; D'Agostino, Ralph; Imperatore, Giuseppina; Saydah, Sharon; Roberts, Alissa; Marcovina, Santica; Mayer‐Davis, Elizabeth J.; Dabelea, Dana; Lawrence, Jean M.; Pihoker, Catherine
Abstract: To assess changes in diabetes autoantibodies (DAs) over time in children and young adults with diabetes and determine whether observed changes were associated with demographic characteristics, clinical parameters and diabetes complications. Participants had DAs measured at baseline (10.3 ± 7.1 months after diabetes diagnosis) and at 12, 24 months and ≥5 years after the baseline measurement. At the ≥5‐year follow‐up, the presence of diabetes complications was assessed. We examined the associations between change in number of positive DAs and changes in individual DA status with the participants' characteristics and clinical parameters over time. Out of 4179 participants, 62% had longitudinal DA data and 51% had complications and longitudinal DA data. In participants with ≥1 baseline positive DA ( n  = 1699), 83.4% remained positive after 7.3 ± 2.3 years duration of diabetes. Decrease in number of positive DAs was associated with longer diabetes duration ( p  = 0.003 for 1 baseline positive DA; p  < 0.001 for 2 baseline positive DAs) and younger age at diagnosis ( p  < 0.001 for 2 baseline positive DAs). No associations were found between change in number of positive DAs in participants with ≥1 baseline positive DA ( n  = 1391) and HbA1c, insulin dose, acute, or chronic complications after 7.7 ± 1.9 years duration of diabetes. DA status likely remains stable in the first 7 years after diabetes diagnosis. Younger age at diabetes diagnosis and longer duration were associated with less persistence of DAs. Measuring DAs after initial presentation may aid in diabetes classification but not likely in predicting the clinical course.